Upaya Wali Kelas Dalam Menerapkan Aturan Kedisiplinan Ibadah Shalat - Najmah, Lailan; Muliati, Indah (An-Nuha, 2024)
Prayer is a medium of communication between a servant and his God. Performing prayers means reflecting one's faith as a sign of religious propagation and a sign of gratitude to Allah SWT. This research aims to find out what the class teacher's efforts are in implementing the disciplinary rules for prayer in class V at SDIT Darul Hikmah, Lembah Melintang District. This research uses a qualitative method with a descriptive approach. Data sources were taken from ten informants through interviews conducted directly in the field consisting of school principals, homeroom teachers, Islamic Religious Education teachers, and students. To strengthen the research data, the author also collected data by observation and documentation. Then all interview data was analyzed by means of data collection, reduction, presentation and drawing conclusions. The results of the analysis show that the class teacher's efforts in implementing the disciplinary rules for student prayer are first, explaining to students the obligation to pray through the school's prayer SOP rules. Second, guiding the implementation of prayer services. Third, control the connecting book. The results of this research can be used as a strategy in forming student prayer discipline.